Innovative android application for anthropometric assessment of nutritional status in boys aged 0-59 months - Alam, Hilda Sulistia; Asriadi, Asriadi (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2024)
Background: Smartphone users in Indonesia mostly use smartphones to access mobile applications rather than mobile websites. As many as 82% of smartphone users in Indonesia access mobile applications while the remaining 9% of users each access mobile websites and websites via desktop. The majority of the population of smartphone users who access mobile applications come from productive age, namely 75% from 18-24 year olds and 79% from 25-34 year olds. The survey results prove that the development of information technology in mobile technology has developed rapidly. These technological developments have resulted in changes and developments in all fields, one of which is the health sector. Objectives: The aim of this research is to design and create Android-based anthropometry of nutritional status aged 0-59 months. which can be downloaded via the cell phone used by Posyandu cadres.Methods:.This research developed an innovative Android application to assess the nutritional status of boys aged 0-59 months using the Waterfall development method in the Software Development Life Cycle (SDLC). This approach starts from requirements analysis, system design, coding, testing, to implementation and maintenance, which is carried out in a linear and gradual manner to ensure that each phase of development runs in a structured manner and produces effective and high-quality applications.Results: The research results show that this anthropometric application significantly increases the efficiency and effectiveness of Posyandu cadre service time. By reducing the need for manual recording and calculations, this application speeds up the process of assessing the nutritional status of children aged 0-59 months, reduces errors, and allows cadres to focus more on direct interactions with mothers and children, thereby improving the overall quality of services.Conclusions: Android-based Anthropometric Application for Nutritional Status Age 0-59 Months is a digital tools.